A modular synthesis approach to multinuclear heterometallic oxo clusters in polyoxometalates. Issue 54 (20th June 2017) - Minato, Takuo; Suzuki, Kosuke; Ohata, Yusuke; Yamaguchi, Kazuya; Mizuno, Noritaka
Abstract : A "modular synthesis approach" to multinuclear heterometallic oxo clusters in lacunary polyoxometalates was successfully developed. Abstract : We report a "modular synthesis approach" to multinuclear heterometallic oxo clusters in lacunary polyoxometalates (POMs). This approach allowed the synthesis of a POM containing a nonanuclear CrMn4 Lu2 Ag2 cluster with the widest variety of metals among the discrete metal oxo clusters prepared to date.